Characteristics of High Saturation Hydrate Reservoirs in the Low-Angle Subduction Area of the Makran Accretionary Prism - Liao, Jing; Liu, Xinxin; Zhao, Qingfang; Gong, Jianming; Yin, Weihan; Li, Sen; Lei, Baohua; Liang, Jie; Muhammad, Khalid; Syed, Waseem Haider (Frontiers in Earth Science, 2022)
To delineate the spatial distribution of high saturation gas hydrate reservoirs in the low-angle subduction areas of the Makran Accretionary Prism, we conducted seismic data interpretation and impedance inversion of gas hydrates in the Makran Accretionary Prism and comprehensively analyzed the characteristics of the high saturation gas hydrate reservoirs in the Nankai Trough in Japan and the Shenhu Area in the South China Sea. The results show that the Makran Accretionary Prism features thick sediments, developed transport systems (i.e., faults and permeable strata), and clear and continuous bottom simulating reflector (BSR). Meanwhile, strong-amplitude reflectors and strong-impedance anomalies coexist in the anticline wing above the BSR. Combined with the proven characteristics of high saturation gas hydrate reservoir, the high saturation gas hydrate reservoirs in the Makran Accretionary Prism are probably mainly distributed in the anticline wings immediately above the BSR. These results provide useful information for the exploration and development of gas hydrate in the low-angle subduction area of the Makran Accretionary Prism